Workshop on applied policy research for scaling innovations in Uzbekistan’s agri-food sector - Akramov, Kamiljon T.; Akhramkhanov, Akmal; Gafurov, Zafar; Egamberdieva, Dilfuza; Rajiv, Sharanya; Dosov, Botir (International Food Policy Research Institute, 2025)
Uzbekistan’s agri-food sector is undergoing rapid transformation driven by structural reforms, growing water scarcity, and the need to build climate resilience across farms of all sizes. Some progress has been made in introducing water-saving irrigation technologies, digital agriculture tools, improved seed systems, mechanization solutions, and cluster-based value chains. These initiatives demonstrate strong potential, yet their scale and impact remain uneven. Fragmented policy implementation, overlapping institutional mandates, and weak coordination between ministries and agencies continue to limit the nationwide adoption of innovative technologies.